2016
DOI: 10.1080/13554794.2016.1175634
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memory and the self in a single-case of chronic unilateral spatial neglect

Abstract: Unilateral spatial neglect (USN) is mainly defined as a condition affecting perception and the mental representation of the environment. However, nothing is known about its impact on the ability to mentally represent one's past and on personal identity. We addressed these questions in a case of chronic USN, DR, a 59-year-old right-handed woman, who underwent a variety of measures exploring the self and autobiographical memory (AM). DR showed preserved self-images and her AM performance was only preserved when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
1
2
0
4
Order By: Relevance
“…A similar effect was found in a case study by Ernst et al (2016) who compared the episodic richness of memories generated to standard autobiographical memory cues in the TEMPau Task (Piolino et al, 2000) with memories cued by 'I am' statements in DR, a patient with chronic Unilateral Spatial Neglect (USN). Although DR's episodic specificity scores were significantly lower than controls in the TEMPau task, her specificity ratings were equivalent to controls when she used 'I am' statements as cues.…”
Section: The Idea That Memory and Self Are Bi-directionally Linked Issupporting
confidence: 60%
See 2 more Smart Citations
“…A similar effect was found in a case study by Ernst et al (2016) who compared the episodic richness of memories generated to standard autobiographical memory cues in the TEMPau Task (Piolino et al, 2000) with memories cued by 'I am' statements in DR, a patient with chronic Unilateral Spatial Neglect (USN). Although DR's episodic specificity scores were significantly lower than controls in the TEMPau task, her specificity ratings were equivalent to controls when she used 'I am' statements as cues.…”
Section: The Idea That Memory and Self Are Bi-directionally Linked Issupporting
confidence: 60%
“…Indeed, autonoetic consciousness (the sense of oneself travelling back in time and re-living past events) is a defining feature of episodic memory (Tulving, 1985) and several studies suggest that self-related memory cues serve to enhance episodic richness (e.g. Ernst et al, 2016, El Haj et al, 2017. Miles et al, (2013) found that participants with dementia produced memories with higher ratings of episodic specificity when they were recalled in an early 20 th century museum setting (surrounded by cues associated with their youth), compared to a control setting of a typical everyday room.…”
Section: The Idea That Memory and Self Are Bi-directionally Linked Ismentioning
confidence: 99%
See 1 more Smart Citation
“…Diante disso, entende-se a importância do estudo do comprometimento da memória decorrente de AVE, mas Carvajal-Castrillón; Arenas (2015) apontam que a memória pode ser classificada em subtipos, de acordo com o tipo de conteúdo armazenado, dentre os quais se destaca a memória autobiográfica (MA). Ernst et al (2016) passado, componente que tem uma estreita relação com o conceito de identidade, pois a formação da identidade se compõe a partir de memórias que definem quem o indivíduo é, além de ser essencial nas relações sociais e na escolha de comportamentos. Segundo Carvajal--Castrillón; Arenas (2015), a MA é composta por todos os eventos que uma pessoa vivencia e, portanto, permite que ela crie um sentimento de identidade.…”
Section: Introductionunclassified
“…A forma de avaliar se esta função foi comprometida ou não e a extensão do comprometimento é através da avaliação neuropsicológica, que, segundo Pavan et al (2015), é uma análise das habilidades neuropsicológicas preservadas e prejudicadas, o que possibilita uma melhor compreensão do caso, seguido do delineamento de um diagnóstico, prognóstico e planejamento da reabilitação. Nota-se a necessidade de realizar essa avaliação para identificar os comprometimentos na memória já que, segundo Ernst et al (2016), um déficit na memória possui grande impacto nas atividades de vida diária, gerando, por exemplo, dificuldade de manter uma conversa e estranhamento em ambientes sociais ou profissionais, nos quais a dificuldade de se lembrar traria no mínimo angústia e frustração. O estudo específico da memória autobiográfica é muito importante pois, de acordo com Boyano (2012), é um componente que envolve conceitos nucleares da psicologia, como identidade pessoal e autoconceito, além de ter um papel relevante na compreensão de transtornos depressivos e estresse pós traumático, por exemplo.…”
Section: Introductionunclassified